NUTRIGENOMICS: HOW GENE SEQUENCING SHAPES PERSONALIZED NUTRITION FOR REVERSING BODY WEIGHT (Journal of Medical & Health Sciences Review, 2025)
Obesity and weight-related disease are on the rise worldwide. Most diets don't work equally for all individuals since bodies react to food differently. Nutrigenomics is a new science that examines how our genes influence how we metabolize food, and how food influences our genes. With advances in gene testing technology, now we can determine why some individuals gain weight more quickly than others via their DNA. This is a review that describes how gene sequencing can be used to plan personalized diets from an individual's own genetic makeup. Such diets could be more successful for weight loss and well-being than normal dietary recommendations. We also look at how other influences such as gut bacteria (microbiome) and how genes are activated or suppressed (epigenetics) influence weight. As of yet, though this area remains under development, the findings up to now have been encouraging. Our genes could be the key to healthy nutrition and weight loss in the years to come.